SHAREHOLDERS' RIGHTS PLANS - THE POISON PILL IN THE U.S. AND CANADA: BACKGROUND AND LEGAL CONSIDERATIONS - Bernier, Jean-François (Revue de droit de l'Université de Sherbrooke)

(untitled) (Revue de Droit de l’Université de Sherbrooke, 1990)
In anticipation of the Quebec Superior Court's ruling on the Caisse de dépôt et placement's judicial challenge to the first Canadian prescription of the "Poison Pill" defense mecanism by Inco Ltd.'s board of directors in late 1988 to alter unwelcomed take-over attempts, the author examines, in the first part of his study, the origin and the various legal considerations surrounding the U.S. developped remedy. In the second part, the author focuses on the prevailing Canadian legal environment from both a corporate and securities standpoint to question the legal validity of the "Poison Pill" in light of its growing popularity as the medication of choice for Canada's directors who whish to insure their preservation of corporate control.